2021
DOI: 10.15291/geoadria.3409
|View full text |Cite
|
Sign up to set email alerts
|

Pristupi vrednovanja krajobraza

Abstract: Polazište za istraživanje ovoga rada je u širokom spektru metoda kojima se mogu vrednovati krajobrazne kvalitete. Svrha rada je utvrđivanje prednosti i nedostataka često korištenih pristupa za vrednovanje krajobraza. Na odabranom području istraživanja, otoku Rabu, radom je identificirano petnaest krajobraznih područja te su određena tri pristupa za vrednovanje kvaliteta krajobraza: 1. jedan temeljen isključivo na vrednovanju ranjivosti kvaliteta krajobraza, a dva na procjeni osjetljivosti krajobraza; 2. prekla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Selecting key observation points for visual assessment also requires scientific justification [29]. Based on three landscape quality assessment methods, namely landscape vulnerability assessment, landscape sensitivity assessment, and direct landscape assessment, previous studies have found that any of these methods can identify the area with the highest landscape quality within the same region [30].…”
Section: B Dynamic Visual Landscape Restoration and Evaluationmentioning
confidence: 99%
“…Selecting key observation points for visual assessment also requires scientific justification [29]. Based on three landscape quality assessment methods, namely landscape vulnerability assessment, landscape sensitivity assessment, and direct landscape assessment, previous studies have found that any of these methods can identify the area with the highest landscape quality within the same region [30].…”
Section: B Dynamic Visual Landscape Restoration and Evaluationmentioning
confidence: 99%
“…A landscape sensitivity assessment is not a definitive approach, and different methods can be used depending on the needs. Nowadays, expert evaluation and geographic information system (GIS) analysis are used to determine landscape sensitivity [7], and the high-sensitivity zones identified by each technique are essentially the same [8]. Landscape sensitivity has been applied to landscape management in some countries.…”
Section: Introductionmentioning
confidence: 99%
“…Warnock and Griffiths [17] created the Living Landscapes Project (LLP) based on LCA by classifying the landscape into natural, cultural, and visual dimensions. Bogovac et al [8] modeled landscape vulnerability by categorizing the landscape into natural, cultural-historical, and visual experiences. Manolaki et al [18] categorized the landscape as ecological, cultural, and visual to assess the landscape sensitivity of Cyprus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation